2003
DOI: 10.1073/pnas.1132092100
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells and cholinergic neurons: Regulation by immunolesion and treatment with mitogens, retinoic acid, and nerve growth factor

Abstract: Degenerative diseases represent a severe problem because of the very limited repair capability of the nervous system. To test the potential of using stem cells in the adult central nervous system as ''brain-marrow'' for repair purposes, several issues need to be clarified. We are exploring the possibility of influencing, in vivo, proliferation, migration, and phenotype lineage of stem cells in the brain of adult animals with selective neural lesions by exogenous administration (alone or in combination) of horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…We found an up-regulation of neurotrophic factors, including the nonneuronal growth factors, bFGF-2 and EGF. These two factors are involved in in vivo proliferation and migration of neuronal progenitor cells and can provide additional pathways for brain repair (52). Overexpression of IL-10 served in part to affect microglia inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…We found an up-regulation of neurotrophic factors, including the nonneuronal growth factors, bFGF-2 and EGF. These two factors are involved in in vivo proliferation and migration of neuronal progenitor cells and can provide additional pathways for brain repair (52). Overexpression of IL-10 served in part to affect microglia inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Neural degeneration by a disease can have drastic effects on other body tissues as neurons have a paltrier ability to regenerate or to repair (Calza et al, 2003). This has been one of the major short comings of producing drugs to reverse the effects neuro degeneration.…”
Section: Retinoic Acid Towards Stem Cell Proliferation and Productionmentioning
confidence: 99%
“…Nevertheless the degenerated tissue is not replaced as immature nerve cells die before maturation (Arvidsson et al, 2002). Main governing factors for this inability for regeneration can be the hostile microenvironment, stem cell molecular mechanisms and inactive survival mechanisms or the type of lesion (Calza et al, 2003). Novel studies have shown that Neuron Growth Factor (NFG) and RA collectively aid the regulation of neural cell differentiation and juvenescence in the early growth stages of the human body (Bai et al, 2007;Zhang et al, 2010;Holst et al, 1997).…”
Section: Retinoic Acid Towards Stem Cell Proliferation and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] The mechanisms underlying this neuroprotective role of NGF are not fully characterized, but several studies have shown its positive influence on cerebral blood flow, cellular Ca2+ homeostasis, and antioxidant activity. [13,14,[17][18][19] The purpose of our research was to analyze the association between the serum beta-NGF level and the severity of ND in children in the first year of life.…”
Section: Introductionmentioning
confidence: 99%